2016
DOI: 10.1016/j.electacta.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Efficient nitrogen removal by simultaneous photoelectrocatalytic oxidation and electrochemically active biofilm denitrification

Abstract: A novel nitrogen removal strategy, the combined photoelectrocatalytic oxidation and autotrophic biofilm denitrification, was developed to achieve simultaneous NH 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…PEC degradation of ammonia in the presence of chloride ions at both acidic and basic pH conditions on the TNT anode was markedly enhanced by 14.8 times reported by Xiao et al It is normally found that nitrite or nitrate ions are also produced during the PEC oxidation, which are undesirable for the complete denitrification process. Recently, Wang et al proposed simultaneous PEC oxidation of ammonia on anode and reduction of nitrate by electrochemically active biofilm on cathode in a single reactor . Ji et al have developed a PEC–chlorine system utilizing a visible light active WO 3 nanoplate array as a photoanode .…”
Section: Electrochemical Oxidation Of Ammoniamentioning
confidence: 99%
“…PEC degradation of ammonia in the presence of chloride ions at both acidic and basic pH conditions on the TNT anode was markedly enhanced by 14.8 times reported by Xiao et al It is normally found that nitrite or nitrate ions are also produced during the PEC oxidation, which are undesirable for the complete denitrification process. Recently, Wang et al proposed simultaneous PEC oxidation of ammonia on anode and reduction of nitrate by electrochemically active biofilm on cathode in a single reactor . Ji et al have developed a PEC–chlorine system utilizing a visible light active WO 3 nanoplate array as a photoanode .…”
Section: Electrochemical Oxidation Of Ammoniamentioning
confidence: 99%
“…On the contrary, microbial denitrification usually has high selectivity. Regarding the EDeN, ammonium formation was reported to be at a very low level or even not detected. , Considering that the conduction band of TiO 2 (−0.5 V vs SHE at pH 7) lies at an energy level that is noticeably higher than that of nitrate reduction, the photoexcited electrons should have energy high enough to drive EDeN without additional energy input, such as power supply as in the previous study . Therefore, we hypothesize that combining the TiO 2 semiconductor system with the EDeN will gain a high selectivity for reducing nitrate to N 2 , and the occurrence of this process can solely rely on the illuminating dose.…”
Section: Introductionmentioning
confidence: 73%
“…Since this wavelength is covered by the spectrum of sunlight, PEDeN is also expected to be worked under sunlight irradiation. However, the nitrate removal rate could be limited in the present PEDeN system because TiO 2 merely responds to UV light (only accounts for 4% of the solar energy) due to the relatively large band gap (∼3.2 eV) . Fortunately, many visible light response approaches, such as metal/nonmetal doping, dye sensitization, and coupling semiconductors, can help PEDeN work under the extended light spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations